PERAN MANAJEMEN SUMBER DAYA PENDIDIKAN TERHADAP MUTU PENDIDIKAN (STUDI KASUS DI TK TAHFIDZ AL- QUDS SAMARINDA) - Salsabila, Nada; Bahrani, Bahrani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The role of educational resource management in improving the quality of education at Tahfidz Al-Quds Samarinda Kindergarten, focusing on three main aspects: human resource management, facilities and infrastructure, and financing. These three aspects are important foundations in supporting the achievement of the Al-Qur'an memorization program at the PAUD level. The approach used is qualitative descriptive with a case study method. Data were obtained through observation, in-depth interviews with the principal, teachers, and parents of students, as well as curriculum documentation and school reports. The results of the study indicate that human resource management is carried out selectively with ongoing training, facilities and infrastructure sufficiently support tahfidz and Montessori learning, despite limited open space, and financing management is carried out transparently and accountably. These three aspects have been proven to contribute positively to improving the quality of education, such as student memorization, Islamic character, and learning independence. The novelty of this study provides an integrative picture of the importance of structured resource management in supporting the quality of early childhood Islamic education, as well as being an example of good practice for similar PAUD institutions.